Hdac1 as an early determinant of intermediate-exhausted CD8 + T cell fate in chronic viral infection - Wei Hu; Shengen Shawn Hu; Shaoqi Zhu; Weiqun Peng; Vladimir P. Badovinac; Chongzhi Zang; Xudong Zhao; Hai-Hui Xue (Proceedings of the National Academy of Sciences, 2025)
The exhausted CD8 + T (T EX ) cells consist of distinct subsets including Tcf1 + stem-like, Tcf1 – Cx3cr1 + intermediate (T EX -int) and Tcf1 – Cx3cr1 – terminally exhausted cells; yet, epigenetic determinants of T EX subset differentiation remain incompletely understood. Using chronic viral infection, we show that histone deacetylase 1 (Hdac1) was specifically required for the formation of antigen-specific T EX -int cells at the effector phase of responses. Single-cell transcriptomics validated that Hdac1 deficiency depleted T EX -int cells and revealed that Hdac1 was critical for positive regulation of T EX -int-characteristic genes, including Cx3cr1 , Cxcr6 , and Klf2 . Furthermore, profiling chromatin accessibility landscape in T EX subsets demonstrated that loss of Hdac1 resulted in a prevalent increase in chromatin open state, as evidently observed at the exhaustion program genes, which were linked to induced expression of exhaustion-inducing Tox transcription factor, PD1 and Lag3 coinhibitory receptors in T EX cells. Hdac1 thus has dual regulatory functions: promoting T EX -int cell fate and preventing excessive activation of the exhaustion program to curtail uncontrolled virus replication.